Halal logistics in a rentier state: An observation - Mohamed Syazwan Ab Talib; Siti Norida Wahab (Modern Supply Chain Research and Applications, 2021)
Purpose - Brunei Darussalam, a rentier state, aims to be one of the leading nations in the global halal industry, and logistics play a key role in realising the goal. However, even though logistics is a vital aspect of the halal supply chain, little is known about the halal logistics scene in Brunei. Therefore, this paper aims to discuss and uncover the various strengths, weaknesses, opportunities and threats surrounding the country's halal logistics sector. Design/methodology/approach - The paper employs a subjective environmental scanning approach and a SWOT analysis technique through the author's observation of Brunei's halal logistics ecosystem from both intrinsic and extrinsic lenses. Findings - The paper argues that substantial institutional support is an apparent strength, but the lack of halal logistics experts is a distinct weakness. Meanwhile, the growing use of technology presents an opportunity for the industry, but formidable regional competition poses a significant threat. Research limitations/implications - Despite the paper's qualitative approach, insights from it could offer a better understanding of halal logistics in Brunei and serve a platform for future research endeavours. Originality/value - Being a rentier state that depends on a non-renewable source, this paper offers an alternative strategy to diversify the economy and venture into the halal economy.
Keywords: 650; Logistics management; Halal logistics; Halal supply chain management; SWOT analysis